Formalin Effectiveness Test With Various Concentration of Clostridium perfringens Growth Inhibition Evaluation Study of Preserving Bodies Method - Nadiya, Jelita Numa (Jurnal Forensik dan Medikolegal Indonesia, 2019)
Death is the cessation of function of the circulatory system and respiratory system, or brain stem death has occurred. Decomposition is natural process that occur shortly after death. The main bacteria involved in the decomposition process is Clostridium perfringens. The process of decomposition sometimes need to be inhibited by the preservation bodies. Preserving the corpse is a medical procedure for the provision of certain chemicals such as formalin. This study was conducted to determine the ability of formalin in inhibiting the growth of C.perfringens and the effective concentration of formalin. This was an experimental study with post test only and contol group design. The research examined the effects of formalin that inhibit the growth of C.perfringens. The concentration of formalin was given at 2%, 4%, 6%, 8%, and 10% in liquid medium Nutrient Broth. C.perfringens were incubated for 24 hours at 37°C, then planted in agar plate with spread plate method to determine the growth of bacteria. Bacterial growth was calculated by colony counter then the percentage inhibition was determined. The effective concentration of formalin was determined by Minimum Inhibitory Concentration 50 (MIC50) and the data obtained were analyzed using parametric tests One Way Annova. The results of this study indicated that the concentration of formalin 6% has the ability to inhibit 52% of bacterial growth. Thus formalin 6% could be regarded as the effective concentration. One-Way Annova test showed the value p = 0.000 (p <0.05). In conclusion, formalin as a corpse preservation solution were able to inhibit the growth of bacteria C. Perfringens with effective concentration of 6%.